Technological Progress and Market Growth : An Empirical Study Based on the Quality-Ladder Approach - Hariolf Grupp; Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2004)
This paper develops an extended version of the quality-ladder model by allowing for heterogeneous markets. Based on this model, it presents an empirical analysis of innovation-based growth at the market level using a technometric measurement concept. It can be shown that a growth-promoting effect due to technological progress in a particular, single year is observed after between two and up to seven years. This is true not only for highly innovative markets, but also for those in which fewer R&D resources are invested.
urn:nbn:de:bsz:21-opus-18275
Keywords: O33; L16; 330; Innovative Activities; Quality Ladders; Endogenous Market Growth; Technometrics; Wachstumsbranche; Produktqualität; Innovation; Technischer Fortschritt; Neue Wachstumstheorie; Schätzung; Welt